Tumor therapy based on self‐assembling peptides nanotechnology. Issue 4 (9th August 2020) - Ma, Xiaoyan; Xing, Ruirui; Yuan, Chengqian; Ogino, Kenji; Yan, Xuehai
Abstract: Self‐assembling peptides display great potential in biological and medical applications, especially tumor therapy with noninvasive ways. The rapid expansion of self‐assembling peptides is almost on account of their favorable biocompatibility, tumor microenvironment responsiveness, multivalency, and structural versatility. With taking full advantage of self‐assembling peptide peculiarities, peptide‐based nanomaterials are applied for delivery carriers, chemotherapy, immunotherapy, and noninvasive tumor treatments including photothermal therapy (PTT), photodynamic therapy (PDT), and sonodynamic therapy (SDT). In addition, immunogenic cell death of tumor cells originating from PDT and SDT, and the necrosis of tumor cells due to PTT can elicit some degree of immune responses. Therefore, synergistic therapy has served as a more effective and powerful strategy for tumor therapy. Importantly, self‐assembling peptides are capable of subtly making combination of various treatments. This review outlines biomedical applications of nanomaterials based on self‐assembling peptides with emphasizing variegated treatment methods. Abstract : Self‐assembling peptides display great potential in biomedical applications, especially tumor therapy with noninvasive ways. Interestingly, self‐assembling peptides are capable of subtly making combination of various treatment methods for achieving maximum therapeutic efficacy.